Odpowiedzi

2010-03-22T18:26:36+01:00
A) 3(3-x)+2x=8-2(x-1)
9 - 3x + 2x = 8 - 2x + 2
9 - x = 10 - 2x / +2x
9 + x = 10 / -9
x = 1

b) 4x+5-(3x+6)=2(2+x)-4
4x + 5 - 3x - 6 = 4 + 2x - 4
x - 1 = 2x / -x
x = -1

c) 4-5(3-x)=-x(3-2x)
4 - 15 + 5x = -3x + 2x²
-11 + 5x = -3x + 2x² / +3x
-11 + 8x = 2x² (nie wiem jak dalej rozwiązać)

d) x-(7+2x)=2(x-1)+1
x - 7 - 2x = 2x - 2 + 1
- x - 7 = 2x - 1 / +x
-7 = 3x - 1 / +1
-6 = 3x / :3
x = -2
Najlepsza Odpowiedź!
2010-03-22T18:28:35+01:00
A) 9-3x+2x=8-2x+2
-x+2x=1
x=1
b) 4x+5-3x-6=4+2x-4
-x=1/:(-1)
x=-1
c)4-15+5x=-3x+2x²
-11+5x=-3x+2x²
-11=-8x+2x²
-8x+2x²+11=0
2x²-8x+11=0
Δ=64-88
Δ=-24
brak rozwiązania
d) x-7-2x=2x-2+1
-x-2x=-1+7
-3x=6/:(-3)
x=-2